Perceptions on Critical Urban Issues in the COVID-19 Pandemic Crises - Muritala Olaniyi Oke; Ibrahim Dinju Choji; Oluseyi Oshinfowokan (Department of Urban and Regional Planning, Universitas Diponegoro, 2021)
COVID-19 Pandemic crises have further challenged the achievement of sustainable urban or cities development as they are now a potential threat for quick transmission of disease between humans and other urban areas due to their connectivity via rail, flights, or roads. The absence of sustainability features of smart cities such as well numbered buildings, street naming for effective contact tracing, and tracing index contact of infected persons prevents effective infection management. The COVID-19 disease has therefore brought out the need to address the emerging urban challenges been faced, drawing from the perception of the urban dwellers, especially on what and how to achieve efficient management of pandemic in the urban areas, building urban resilience, and achieving sustainable development goal (SDG) 11 target of safe, inclusive and sustainable cities. Thus, this paper aims to interrogate the urban dwellers' perception in Jakarta, Indonesia, and Lagos, Nigeria, on emerging urban issues brought out by the COVID – 19 pandemic management and how they could be managed in the future. The study utilizes a questionnaire developed in the google form and distributed using email and WhatsApp platforms to three hundred respondents, One hundred and fifty respondents in each city, picked by their expertise and official responsibility in the urban-related field. The results reveal that key urban planning issues such as weak health systems, crowd management, adherence to government orders on handwashing and sanitation, social distancing, and socio-cultural issues need to be given utmost attention. Recommendations were made in line with effecting an integrated planning policy, citizen reorientation, and the need to re-plan these cities, amongst others.